Meningkatkan Keterampilan Berpikir Kritis, Dan Hasil Belajar Siswa SD Menggunakan Model PEMENANG - Titi Aryani; Raihanah Sari (CV. ITTC INDONESIA, 2023)
The problem in this research is the low level of critical thinking skills and student learning outcomes in social studies learning. To overcome this, use the PEMENANG model in the learning process. The purpose of this research is to analyze critical thinking skills and student learning outcomes. Researchers used PTK, held 3 meetings in class 5 at SDI Al-Munawwarah with a total of 15 students. Researchers use a qualitative approach, with qualitative and quantitative data types. Data was analyzed qualitatively, namely critical thinking skills, and quantitatively, namely learning outcomes. The results of this research show that Critical Thinking Skills at meeting 1 obtained 40% with the